Correction: Artificial miniaturized luminescent materials based on perylene-covered glass surfaces. (27th September 2017) - Mameri, Samir
Abstract : Correction for 'Artificial miniaturized luminescent materials based on perylene-covered glass surfaces' by Samir Mameri et al., New J. Chem., 2017, 41, 6083–6088.